(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
In this work, modern approach was demonstrated which is improving the performance of gas sensors that utilize the quartz crystal microbalance technique. The gas sensors based on quartz crystal microbalance (QCM) are one of the common methods using for gas sensor applications. Although, these QCM sensors posses high sensitivities, its ability to discriminate the target gas still need to develop. It does not have the ability to identify or distinguish the type of gas. The idea of this work depends on investigating and invest the kinetics of the diffusion and adsorption thermodynamics gas molecules to identify gas species. So, the relationship between the parameter of the dynamic adsorption and chemisorption thermodynamic parameter were employed to know the concentration and type of the gases. The sensor was coated Polydimethylsiloxane (PDMS) ultrathin films are prepared via spin coating system, and micro incision via lithographic methods has been created on the PDMS film. In order to enhance the selectivity of the sensor. The outcome data prove the methology was working and considerable. Nevertheless, there are insufficiency. The gas molecules distinction was made possible by analysis the response signal. In particular, observing and taking into account the difference and change in the time constant. Where note a difference in the time constant due to present of the micro-pattern layer.